Bio‐purification of domestic wastewater through constructed wetland planted with Paspalidium flavidum. (20th January 2022) - Rehman, Abdul; Zakir, Bushra; Anees, Muhammad; Naz, Iffat; Alhewairini, Saleh S.; Sehar, Shama
Abstract: The current study was aimed to designed laboratory scale constructed wetland (CW) for the treatment of domestic wastewater under temperature range (18–38°C) and hydraulic retention times (24 and 48 h). Besides, the soil of vegetative unit of CW was assessed using conventional culturing techniques, and 13 different bacterial species ( Escherichia coli, Micrococcus, Pseudomonas, Proteus, Klebsiella, Streptococcus, Alcaligenes, Salmonella, Bacillus, Enterobacter, Staphylococcus, Shigella and Corynebacterium spp.) were determined. The pathogenic microbial load was high in influent samples, but after treatment, about 73.1–99.7% and 43.5–86.7% reduction in CFU/ml and MPN/100 ml index, respectively, were observed. Moreover, the organic loads in terms of COD, TDS, TSS, and turbidity were high in all influent samples, but after treatment, average percentage removal in different physico‐chemical parameters was observed during overall treatment operations, that is, COD (59.7–65.6%), TDS (59.6–76.8%), TSS (64.9–76.7%), and turbidity (72.7–91.6%), while pH of the effluent samples was observed in the prescribed limits. It was concluded that laboratory scale CW using natural flora Paspalidium flavidum and bacterial species was efficient in the reduction of different pollution indicators and hence a best option to be modified on pilot‐scale for wastewater treatment in the rural regions of Peshawar. Practitioner Points: Role of retention times on performance of CW were studied. The commonly existing vegetation was utilized to treat domestic waste water. Both vegetations and HRT are key ingredients in obtaining high treatment efficiency. Abstract : In this work, laboratory scale constructed wetland (CW) was designed for the treatment of domestic waste water. The performance evaluation of CW planted with Paspalidium flavidum was recorded at different temperatures and retention times. Various physico‐chemical parameters were analyzed and the treatment efficiencies were recorded as COD (59.7–65.6%), TDS (59.6–76.8%), TSS (64.9–76.7%), and turbidity (72.7–91.6%), respectively.